A Correlational Analysis between Students’ Proficiency in English Language and their Academic Performance in Agricultural Science in FCT, Abuja (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study investigated the correlation between students' English language proficiency and their academic performance in Agricultural Science among senior secondary school students in the Federal Capital Territory (FCT), Abuja. A quantitative research design, specifically a correlational survey, was employed. A sample of 300 Senior Secondary School (SSS) II students was randomly selected from six public secondary schools across the FCT. Data were collected using two instruments: an English Language Proficiency Test (ELPT) and students' academic records in Agricultural Science from the preceding term. The ELPT, developed by the researcher and validated by language experts, comprised multiple-choice questions assessing grammar, vocabulary, and comprehension. Academic performance in Agricultural Science was measured by students' scores in their end-of-term examinations. Pearson Product-Moment Correlation Coefficient was used to analyse the relationship between the two variables. The findings revealed a significant positive correlation between English language proficiency and academic performance in Agricultural Science. This finding was predicated on the calculated r-value which is r=0.65 and the p-value associated with this correlation which is less than the chosen significance level (p